Factors that influence oral health problems: a study among public at urban transformational centre, Melaka / Aniq Ekmal Dolfatah and Nor ‘Ashikin Jamil - Dolfatah, Aniq Ekmal; Jamil, Nor ‘Ashikin (Faculty of Administrative Science and Policy Studies, 2014)
The study seeks to determine the factors that influence oral health problems. A sample 357 of public at Urban Transformational Centre, Melaka (UTC, Melaka) district had been selected for this study. The findings showed that the independent variables or factors that support the researchers’ hypothesis are knowledge on oral care, practices of oral care, and attitude toward oral care. All the three factors determine their relationship with the factors that influence oral health problems among public at UTC, Melaka. Convenient sampling technique will be used in order to distribute the questionnaires to selected respondents. Based on the finding, practices of oral care are the most contributors to the factors that influence oral health problems. While, all the three factors (knowledge on oral care, practices of oral care, and attitude toward oral care) have a significant relationship with the oral health problems. This is due to the result of correlation coefficient that has been used. In conclusion the study has been successfully implemented and shows that three factors has a relationship with oral health problems.